2003
DOI: 10.1097/00000542-200311000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the LMA-Classic ™ with the New Disposable Soft Seal Laryngeal Mask in Spontaneously Breathing Adult Patients

Abstract: In spontaneously breathing adult patients requiring a size 4 laryngeal mask airway, the new disposable Soft Seal LM device is an acceptable alternative to the reusable LMA-Classic trade mark, resulting in a good laryngeal seal and offering similar clinical performance. Cuff pressures increase substantially when the LMA-Classic is used but not when using the Soft Seal LM. There was less trauma to patients using the Soft Seal LM, as assessed by the incidence of sore throat in the early postoperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
41
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 21 publications
10
41
3
Order By: Relevance
“…Studies comparing the LMA-Unique TM and the Portex Soft Seal TM with the LMA Classic have demonstrated that these single-use devices have similar clinical effectiveness and may be acceptable alternatives [6][7][8]. The Ambu Ò AuraOnce TM Laryngeal Mask (Ambu A ⁄ S, Ballerup, Denmark) is claimed to have advantages over competitors.…”
mentioning
confidence: 99%
“…Studies comparing the LMA-Unique TM and the Portex Soft Seal TM with the LMA Classic have demonstrated that these single-use devices have similar clinical effectiveness and may be acceptable alternatives [6][7][8]. The Ambu Ò AuraOnce TM Laryngeal Mask (Ambu A ⁄ S, Ballerup, Denmark) is claimed to have advantages over competitors.…”
mentioning
confidence: 99%
“…Theoretically, the wider shaft and absence of cross-bars might make tracheal intubation through this device easier than through the CLMA. Van Zundert et al have recently studied the ease of placement of the PLMA and found it to be similar to the CLMA [6]. Although they used the fibrescope to establish the view of the vocal cords through the PLMA, they did not assess the ease of fibreoptic-assisted tracheal intubation through the PLMA.…”
mentioning
confidence: 99%
“…However, previous reports suggested that because disposable LMADs, including the Solus TM , have a deeper bowl, ventilation is well maintained despite the absence of epiglottic bars. 2,3 In this case, the FOB passed under the epiglottis with ease, which makes obstruction by the epiglottis improbable.…”
Section: To the Editormentioning
confidence: 96%
“…However, previous reports suggested that because disposable LMADs, including the Solus TM , have a deeper bowl, ventilation is well maintained despite the absence of epiglottic bars. 2,3 In this case, the FOB passed under the epiglottis with ease, which makes obstruction by the epiglottis improbable.Second, the presence of a cuff and the shape and location of the bowl should be considered. The space between the tongue and posterior pharyngeal wall was probably narrow in this patient, becoming narrower because of laryngopharyngeal edema caused by GERD.…”
mentioning
confidence: 96%